Reckoning with markets : the role of moral reflection in economics - Halteman, Jim.; Noell, Edd. (Oxford : Oxford University Press, 2012)
This book presents the notion that economic thinking cannot escape value judgements at any level and that this understanding has been the dominant view throughout most of history. It shows how, from ancient times, people who thought about economic matters integrated moral reflection into their thinking.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 18, 2012).
Keywords: Economics -- Moral and ethical aspects